Answer:
[tex]y' = [t^{(t+2)\cdot (t + 6)}]\cdot \left[(2\cdot t + 8)\cdot \ln t + \frac{t^{2}+8\cdot t + 12}{t} \right][/tex]
Step-by-step explanation:
The function is:
[tex]y = t^{(t+2)\cdot (t+6)}[/tex]
By using natural logarithmics and algebraic handling on both sides:
[tex]\ln y = (t+2)\cdot (t+ 6)\cdot \ln t[/tex]
[tex]\ln y = (t^{2}+8\cdot t + 12)\cdot \ln t[/tex]
The logarithmic differentiation is:
[tex]\frac{1}{y}\cdot y' = (2\cdot t + 8)\cdot \ln t + \frac{t^{2}+8\cdot t + 12}{t}[/tex]
[tex]y' = y\cdot \left[(2\cdot t + 8)\cdot \ln t + \frac{t^{2}+8\cdot t + 12}{t} \right][/tex]
[tex]y' = [t^{(t+2)\cdot (t + 6)}]\cdot \left[(2\cdot t + 8)\cdot \ln t + \frac{t^{2}+8\cdot t + 12}{t} \right][/tex]